Lipidomics profiles of human spermatozoa: insights into capacitation and acrosome reaction using UPLC-MS-based approach - Cheng, Xiaohong; Xie, Haifeng; Xiong, Yuping; Sun, Peibei; Xue, Yamei; Li, Kun (Frontiers in Endocrinology, 2023)
Lipidomics elucidates the roles of lipids in both physiological and pathological processes, intersecting with many diseases and cellular functions. The maintenance of lipid homeostasis, essential for cell health, significantly influences the survival, maturation, and functionality of sperm during fertilization. While capacitation and the acrosome reaction, key processes before fertilization, involve substantial lipidomic alterations, a comprehensive understanding of the changes in human spermatozoa's lipidomic profiles during these processes remains unknown. This study aims to elucidate global lipidomic changes during capacitation and the acrosome reaction in human sperm, employing an untargeted lipidomic strategy using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Twelve semen specimens, exceeding the WHO reference values for semen parameters, were collected. After discontinuous density gradient separation, sperm concentration was adjusted to 2 x 10 6 cells/ml and divided into three groups: uncapacitated, capacitated, and acrosomereacted. UPLC-MS analysis was performed after lipid extraction from these groups.Spectral peak alignment and statistical analysis, utilizing unsupervised principal component analysis (PCA), bidirectional orthogonal partial least squares discriminant analysis (O2PLS-DA) analysis, and supervised partial least-squares-latent structure discriminate analysis (PLS-DA), were employed to identify the most discriminative lipids. The result showed significant lipidomic alterations in A23187-induced acrosome-reacted sperm compared to uncapacitated and/or capacitated sperm. These encompassed increases in PI 44:10, LPS 20:4, LPA 20:5, and LPE 20:4, PC 40:6, PS 35:4, PA 29:1, In conclusion, this study offers novel insights into lipidomic changes associated with capacitation and the acrosome reaction in human sperm, which are closely related to male reproduction. Furthermore, this research highlights the effective utility of UPLC-MS-based lipidomics for exploring diverse physiological states in sperm.